Perbandingan efek latihan intensitas sedang dan tinggi akut pada sekresi protein -1 yang tidak terpisah - Merawati, Desiana; Sugiharto, Sugiharto; Pranoto, Adi; Andiana, Olivia; Angga, Prayogi Dwina; Desiana, Desiana (Universitas Nusantara PGRI Kediri, 2022)
Physical activities accelerate the secretion of the uncoupling protein-1 (UCP-1), which reduces the risk of metabolic disorders and the prevalence of obesity. This research aimed to investigate the effects of acute physical activities on UCP-1 secretion. A total of 20 males (aged between 19-20 years old) were divided into groups with either a 30-minute moderate-intensity exercise (MIE) or high-intensity exercise (HIE). The UCP-1 expression was measured using Enzyme-Linked Immunosorbent Assay (ELISA) (pre and 5 minutes post the exercise). The pre and post-UCP-1 data in each group were compared with a paired t-test, while pre and post UCP data between groups were analyzed using the Independent-Sample T-test. The pre and post test UCP-1 in the MIE was (4.16±0.89) ng/mL and (4.55±1.36) ng/mL (P>0.05), while the pre and post test UCP-1 in the HIE were (4.09±0.53) ng/mL and (5.06±1.02) (P<0.05). No significant difference in pretest UCP-1, however was found between groups (P>0.05) and posted UCP-1 (P>0.05). In conclusion, 30 minutes of high-intensity exercise is required to increase UCP-1 in young adults significantly.